MODERN TECHNOLOGIES OF MAKING SCHOOL CLOTHES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes an improvement in the technology of manufacturing school clothes, restoring and modeling the normal posture of the student. A school vest is proposed as such clothing. The creation of school clothes, especially for students of primary school age, requires an integrated approach that takes into account the specifics of the operation of this type of clothing.